THE EFFECTIVENESS OF STORY TELLING AND STORY READING METHODS IN TEACHING SPEAKING - Khaerana, Andi ST Aldilah; Nurdin, Nadya Nurhidayah (ETERNAL (English, Teaching, Learning, and Research Journal), 2018)
This research aims to find out the effectiveness of story telling and story reading methods in teaching speaking. The researchers applied comparative study method which aims at finding out the comparative effectiveness between the application of storytelling and story reading method in teaching speaking skill. The researchers apply experimental design that involves two groups; storytelling and story reading method in pretest, treatment and posttest. The subject in this research will consist of the 2nd semester students of Speaking 2 class of STKIP YPUP Makassar. There would be two variables in this research, independent and dependent variable. The independent variable is the effectiveness of story reading and story telling, while the dependent variable includes the students’ speaking ability. The result shows that there is no method which more effective between storytelling and story reading methods in teaching speaking. This conclusion refers to the overall of the students’ speaking achievement score. But based on the speaking categories investigations namely accuracy, fluency and comprehensibility, the storytelling method is more effective in increasing the students’ accuracy and fluency in speaking, while the story reading method is more effective in improving the students’ comprehensibility.